Commercial adoption of RRIMFLOW short-cut system of exploitation in several NR producing countries - Sivakumaran S; Ismail Tajuddin; Tham F C; Tham F K (Proceedings of IRRDB Conference: NR Industry: Responding to Globalization, 7-8 September 2004, Kunming International Convention & Exhibition Center, China. pp.279-287.)
The RRIMFLOW short-cut system of exploitation (RF) first developed in Malaysia in the early nineties and commercialized in the mid-nineties involves tapping of one eight length of cut once in three or four days in combination with gaseous stimulation applied intermittently at ten day intervals. Data presented from commercial areas in Malaysia which had adopted the system on large hectarages confirms as previously established that the system is very effective in minimizing tree, tapper and land productivity in rubber. The data obtained from plantations in Malaysia which had adopted the sytem on a significant hectarage also proves that it can substantially increase the total productivity of the plantation thus boosting the overall profitability of the plantation. The positive performance of the system over large hectarages planted with a broad spectrum of clones of different ages and varying field conditions confirms that the system can be universally adopted in mature rubber areas with minimal limitations. The RF system has been very effective in increasing the tree productivity by two or three fold on popularly planted clones relative to conventionally tapped trees in Thailand, Indonesia, India and Papua New Guinea. It has also increased the land productivity of clones GT 1 and RRIM 600 above two thousand kilograms per year per hectare in India, Indonsia and Thailand. These data obtained from commercial plantations in other NR producing countries shows that similar clones irrespective of their geographical location display the same mode and degree of yield response to the RF system. The adoption of the RF sysem over a significant hectarage in plantations in Thailand and Indonesia has contributed to marked increase in total yield productivity of the plantation and which under current high selling prices of rubber will translate into huge margins of profitability for the plantations concerned. The inherent positive attributed favourable to wider adoption of the RF system in other NR countries particularly in Thailand and Indonesia are discussed. In addition some of the existing surmountable constraints to wider commercial uptake of the system in these NR countries are also highlighted. It is apparent that the adoption of the RF sysem will be the most ideal approach to increase world production of natural rubber from existing stands of mature rubber in NR producing countries thus satisfying the increasing global demand for NR anticipated over the next couple of years.
Keywords: Economic impact; Malaysia; RF system; RRIMFLOW